PERAN SEKOLAH BAGI PENDIDIKAN PEKERJA ANAK DI DESA REMBITAN KABUPATEN LOMBOK TENGAH - Nursaptini Nursaptini; Syafruddin Syafruddin; Ni Made Novi Suryanti (Universitas Hamzanwadi, 2024)
Child labor (school-age children already working) in tourist areas is a common phenomenon today. This study aims to determine the role of schools in the education of child workers. The study was conducted using a qualitative case study method. The analysis unit targeted by the study was teachers and principals. Subjects were taken using purposive sampling and informant determination using snowball sampling. Observation, interviews, and documentation were carried out in data collection. The data analysis used data analysis developed by Cresswel, namely Spiral analysis. The results of the study showed that children who became child workers received the same education for schools, schools provided the same services and guidance to child workers, and always offered continuous motivation to get an education, in addition to facilitating by lending textbooks to be taken home so that they could be studied in between work activities.